Invasive Chloroplast Population Genetics of Mikania micrantha in China: No Local Adaptation and Negative Correlation between Diversity and Geographic Distance - Wang, Ting; Wang, Zhen; Chen, Guopei; Wang, Chunbo; Su, Yingjuan (Frontiers in Plant Science, 2016)
Two fundamental questions on how invasive species are able to rapidly colonize novel habitat have emerged. One asks whether a negative correlation exists between the genetic diversity of invasive populations and their geographic distance from the origin of introduction. The other is whether selection on the chloroplast genome is important driver of adaptation to novel soil environments. Here, we addressed these questions in a study of the noxious invasive weed, Mikania micrantha, which has rapidly expanded in to southern China after being introduced to Hong Kong in 1884. Seven cpSSRs were used to investigate population genetics in twenty-eight populations of M. micrantha, which produced thirty-nine loci. The soil compositions for these populations, including Mg abundance, were measured. The results showed that M. micrantha possessed relatively high cpSSR variation and differentiation among populations. Multiple diversity indices were quantified, and none was significantly correlated with distance from the origin of introduction. No evidence for “isolation by distance”, significant spatial structure, bottlenecks, nor linkage disequilibrium was detected. We also were unable to identify loci on the chloroplast genome that exhibited patterns of differentiation that would suggest adaptive evolution in response to soil attributes. Soil Mg has only a genome-wide effect instead of being a selective factor, which highlighted the association between Mg and the successful invasion. This study characterizes the role of the chloroplast genome of M. micrantha during its recent invasion of southern China.